2018
DOI: 10.1103/physrevlett.120.193904
|View full text |Cite
|
Sign up to set email alerts
|

Spiral Transformation for High-Resolution and Efficient Sorting of Optical Vortex Modes

Abstract: Mode sorting is an essential function for optical multiplexing systems that exploit the orthogonality of the orbital angular momentum mode space. The familiar log-polar optical transformation provides a simple yet efficient approach whose resolution is, however, restricted by a considerable overlap between adjacent modes resulting from the limited excursion of the phase along a complete circle around the optical vortex axis. We propose and experimentally verify a new optical transformation that maps spirals (i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
94
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(96 citation statements)
references
References 28 publications
0
94
0
2
Order By: Relevance
“…concept and principle. The spiral transformation method has been successfully applied for high resolution sorting of coherent OAM modes of light 10 . In this work we have applied it to OAM mode sorting of spatially incoherent OAM modes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…concept and principle. The spiral transformation method has been successfully applied for high resolution sorting of coherent OAM modes of light 10 . In this work we have applied it to OAM mode sorting of spatially incoherent OAM modes.…”
Section: Resultsmentioning
confidence: 99%
“…However, the most used optical beam is the OAM beam called Laguerre-Gauss (LG) beam 6 which can be decomposed in terms of orthogonal components allowing being space-divided with low inter-modal crosstalk among multiple modes 2,3,7 . This beam has a finite spatial extend and due to its azimuthal phase dependence can be sorted [8][9][10] , being ideal to optical communications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The second element has to correct the relative phase between these copies at the Fourier plane of the fan-out element. [205][206][207] Recent research work has also demonstrated that performing a spiral transformation instead of a log-polar transformation can also improve the resolution of the mode-sorter output. 208 However, all these methods improve resolution at the expense of making the setup more complex.…”
Section: Geometric Transformation Methodsmentioning
confidence: 99%
“…[ 1,2 ] OVs are characterized by a twisting wavefront, phase singularities, orbital angular momentum (OAM), [ 3–6 ] and null intensity in the beam center. These unique properties have been employed in many applications, such as optical communication, [ 7–9 ] optical manipulation, [ 10–14 ] super‐resolution microscopy, [ 15,16 ] quantum information communication, [ 17–19 ] and laser micromachining. [ 4 ] The OAM carried by each photon deliver energy to particles and can cause them to rotate.…”
Section: Introductionmentioning
confidence: 99%